PERANAN PARA PEJABAT SULTAN PEMERINTAHAN SULTAN ASSAIDIS SYARIF HASYIM ABDUL JALIL SAIFUDDIN DI SIAK SRI INDRAPURA (1889-1908) - Anita, Ria; Ibrahim, Bedriati; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The kingdom of Siak is a Malay-style kingdom that was established in 1723 in Buantan with its first king, Raja Kecik who was the son of Mahmud Syah II and his mother Cik Pung. Throughout the establishment of this kingdom there were twelve sultans who led, in this scientific work discussing the Officials of the Sultan during the reign of Sultan Syarif Hasyim in Siak Sri Indrapura. The objectives of this research are (1) To find out the structure of the government of Siak Kingdom in the government of Sultan Syarif Hasyim (2) To find out the role of officials in the reign of Sultan Syarif Hasyim in carrying out their duties. (3) To find out the condition of the Siak Kingdom when officials carry out their roles and duties. (4) To find out the position of the officials when the death of Sultan Syarif Hasyim. The research method used in this study is the interview method and literature. The results of the research on the role of officials who assisted the Sultan in the Sultan Syarif Hasyim's government have been listed and explained in Babul Qawaid based on the Chapters and the articles contained therein. Glory. The kingdom of Siak occurred during the reign of Sultan Syarif Hasyim. During the reign of Sultan Syarif Hasyim, he was also assisted and supported by the Officials of the Siak Kingdom. The position of Kingdom officials after the death / death of Sultan Syarif Hasyim until the appointment of Sultan Syarif Qasyim II, his position has not changed. The officials who were appointed during the reign of Sultan Syarif Hasyim still survive with their respective positions and duties.Key Words: Officials, Sultan Syarif Hasyim, Siak Kingdom